The role of universities in promoting industrial development in Tanzania: The case of Sokoine University of Agriculture in Morogoro Municipality. - Ngunga, Simalike E. (Mzumbe University, 2026)
A dissertation submitted in partial fulfilment of the requirements for award of the degree of Master of Arts in Education (MAED) of the Mzumbe University.